Quyết định số 3465/QĐ-BTP ngày 23/12/2014 Bộ Tư Pháp về việc miễn nhiệm báo cáo viên pháp luật Trung ương - Bộ Tư pháp (2015)
Nội dung Quyết định số 3465/QĐ-BTP ngày 23/12/2014 Bộ Tư Pháp về việc miễn nhiệm báo cáo viên pháp luật Trung ương.